Information, Knowledge, and the Return of Social Physics. Issue 9 (October 2018) - Adolf, Marian T.; Stehr, Nico
The article discusses two vital aspects of the current debate about the societal importance and future role of data, information, and knowledge in the context of social organization, administration, and government. First, it is argued that the debate concerning Big Data suffers from faulty assumptions regarding the societal significance and power of information which needs to be extended to a more comprehensive investigation about the social role of knowledge. Second, the theoretical positions brought forward are illustrated by revisiting an episode from the early history of the social sciences, arguing that misguided ideas about the possibility of "Social Physics" have failed before and are likely to fail again, due to the complexity of social behavior.